LODOS - Going from BIM to CFD via CAD and model abstraction - Porter, S.; Tan, Tele; Wang, Xiangyu; Pareek, Vishnu (Elsevier BV, 2018)
This paper looks at the challenge of performing Computational Fluid Dynamic simulations against models of real world environments and objects. The difficulty for these simulations is the effort required to render complex objects and environments, as well as the computational power required to solve them. To assist with the first problem, this paper presents a process for importing Building Information Models or 3D CAD models into ANSYS workbench, a popular CFD environment in industry. In order to address computational concerns, this paper also introduces and discusses a system, LODOS, designed to aid in importation and set-up of high complexity models by selectively reducing geometric complexity. This paper presents preliminary results from the use of this system to import two Building Information Models into ANSYS Workbench, showing the current strengths of the system, as well as discussing its current limitations.